2013
DOI: 10.1212/wnl.0b013e31827f0fe5
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in the gene encoding p62 in Japanese patients with amyotrophic lateral sclerosis

Abstract: The presence of mutations in this racial population suggests worldwide, common involvement of the SQSTM1 gene in ALS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
46
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(53 citation statements)
references
References 31 publications
5
46
0
Order By: Relevance
“…Analysis of all SQSTM1 variants that are predicted as being pathogenic in published cohorts, [3][4][5][6] and the current study demonstrated that pathogenic SQSTM1 variants are significantly associated with FALS with a combined odds ratio of 3.91 (P MH ¼ 0.0002, Supplementary Table 1). No significant association was found for SALS cases.…”
Section: Identification Of Sqstm1 Sequence Variants In a Uk-fals Cohortsupporting
confidence: 50%
See 1 more Smart Citation
“…Analysis of all SQSTM1 variants that are predicted as being pathogenic in published cohorts, [3][4][5][6] and the current study demonstrated that pathogenic SQSTM1 variants are significantly associated with FALS with a combined odds ratio of 3.91 (P MH ¼ 0.0002, Supplementary Table 1). No significant association was found for SALS cases.…”
Section: Identification Of Sqstm1 Sequence Variants In a Uk-fals Cohortsupporting
confidence: 50%
“…[3][4][5][6] However, because of lack of DNA in multiple members of FALS kindred, to date it has not been proved that any of these mutations are transmitted with disease in ALS. Nevertheless, among the coding mutations is p.(Pro392Leu), which is common in Paget's disease of bone (PDB), 7,8 where there is evidence of transmission of the mutation with disease in multiple kindred.…”
Section: Introductionmentioning
confidence: 99%
“…About 90 % of cases occur sporadically (sALS). The remainder are clearly familial (fALS; Valdmanis et al 2009); the genetic loci identified include genes encoding Cu/Zn-superoxide dismutase (SOD1; Rosen et al 1993), TAR DNA-binding protein 43 (Neumann et al 2006;Arai et al 2006), fused in sarcoma/ translated in liposarcoma (FUS; Kwiatkowski et al 2009;Vance et al 2009), vesicle-associated membrane protein B (Nishimura et al 2004), ubiquilin2 (Deng et al 2011), C9ORF72 (Renton et al 2011;Dejesus-Hernandez et al 2011), p62 (Hirano et al 2013), profilin 1 (Daoud et al 2013) , and RGNEF, a rhoGEF nucleotide exchange factor (Droppelmann et al 2013). Aside from sporadic ALS, this multiplicity of fALS-associated genes points to ALS being a syndrome with multiple initiating factors, yet there are commonalities in the manifestation of disease in patients with either familial or sporadic disease including formation of inclusions, unfolded protein responses, excitotoxicity, calcium dysregulation, mitochondrial dysfunction, oxidative stress, axonal transport defects, disruption of neuromuscular junctions, altered RNA metabolism, disruption of neuron-glia interactions, and inflammatory responses (Boillee et al 2006).…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%
“…Sequestosome 1 (SQSTM1) may represent another potential link between autophagy and ALS, as deletions and point mutations of this gene, encoding the ubiquitin-binding protein p62/SQSTM1, have been detected in ALS (Hirano et al, 2013;Teyssou et al, 2013). p62/SQSTM1 is a scaffold that acts as a mediator between ubiquitinated proteins and LC3-II in order to facilitate their removal via the autophagy (Matsumoto et al, 2011).…”
Section: Accumulation Of Als Pathogenetic Proteins and Autophagymentioning
confidence: 99%